HUBUNGAN MOTIVASI BELAJAR MAHASISWA TERHADAP HASIL BELAJAR PADA MASA PANDEMI COVID-19 TAHUN 2020 - Yopi Wulandhari (JOMIS (Journal of Midwifery Science), 2021)
The education system in Indonesia is undergoing a slight change due to the Covid-19 virus outbreak. To prevent the spread of the virus, learning at higher education institutions that were initially face-to-face was shifted to online learning methods. The existence of changes in this learning system will affect the learning motivation of students which in turn will also affect learning outcomes. The purpose of this study was to determine the relationship between student learning motivation during the Covid-19 pandemic and learning outcomes at the Indragiri Midwifery Academy. This study is an analytic study with a cross-sectional approach (cross-sectional). The independent variable in this study is learning motivation and the dependent variable is learning outcomes. The sample in this study were 38 midwifery students at the Indragiri Midwifery Academy. Sampling with total sampling. Motivation data collection using questionnaires presented in the form of google foam and learning outcomes from the Student Study Results Card (KHS). The results showed that student learning motivation during the Covid-19 pandemic was in the moderate category as many as 32 people (84.2%), while learning outcomes in the poor category were 21 people (55.3%). Analysis of data using statistical test Chy Square test with data processing using SPSS 17.0 obtained p-value 0.378. Thus it can be concluded that there is no significant relationship between the learning motivation of midwifery students during the Covid-19 epidemic and learning outcomes at the Indragiri Midwifery Academy